Health promotion networks in two districts in Bavaria, Germany: an exploratory case study mapping networks with respect to thematic agenda and location - Annika Marie Fehrmann; Annika Marie Fehrmann; Annika Marie Fehrmann; Kathrin Steinbeisser; Kathrin Steinbeisser; Andrea R. Wolff; Michaela Coenen; Michaela Coenen (Frontiers Media S.A., 2023)
IntroductionBuilding networks is an essential part of health promotion. However, network analysis remains relatively unexplored in this field. This study introduces a new technique that maps thematic agendas and geographical locations of health promotion actors.MethodsThis case study used elements of quantitative and qualitative methods to analyse network data. We used empirical data from two networks in Bavaria, a federal state of Germany.ResultsWe identified a total of 55 actors in the first network and 64 actors in the second. We categorized the thematic agenda of actors according to their main field of work: "healthy childhood development," "healthy middle age phase," "healthy ageing," "health equity in all phases of life." One network showed a significant surplus of actors that focus on "healthy ageing." We combined and analysed data from both networks collectively. Two districts with no health promotion actors within their geographical borders were identified. To put geographical gaps into context, data about deprivation and age was included.DiscussionResults identified geographical areas with high need for support from health promotion actors. Through comparison of our results with existing literature, we derived potential network strategies for further successful networking. This study adds a new perspective to characterize health promotion networks by mapping them thematically and geographically. The concept can be used to give health promotion organisations relevant insight into network structures. This can improve decision-making processes concerning partnership strategy and finally lead to a positive health impact. Hence, our findings encourage further development of this technique and other networking methods in the field of health equity and health promotion.